In Vitro Maturation (IVM) of Human Oocytes: Promising Potential, Challenges and Chances for Improvement - Roza Silvia (Fakultas Kedokteran, Universitas Andalas, 2015)
AbstractIn Vitro Maturation (IVM) of human oocytes is an innovation in Assisted Reproductive Technology (ART). It is believed more patient-friendly than conventional In Vitro Fertilization (IVF) method. It is a simple protocol that needs only less injection of ovarian stimulation for the patients and fewer blood sample and ultrasound scans, so this technique may become more favorable. Patients are also prevented from higher cost treatments and quite long control in the hospital. However, there are some problems to be addressed, such as how to improve the success rate, how to assure the safety and to avoid the health risk for the offsprings. Modification in IVM medium and optimizing the IVM protocols have increased the results in some studies. However, further investigation related to all aspects influencing the human oocyte maturation in vitro is still needed to make it enable to be a routine practice in ART centers for a defined group.Kata kunci: in vitro maturation, human oocyte, in vitro fertilization, assisted reproductive technology AbstrakMaturasi oosit in vitro atau In Vitro Maturation (IVM) terhadap oosit manusia merupakan suatu inovasi dalam Teknologi Reproduksi Berbantu (TRB). Teknik ini dianggap lebih nyaman bagi pasien dibandingkan dengan metode Fertilisasi In Vitro (FIV) konvensional. Metode IVM ini sederhana dan hanya membutuhkan lebih sedikit penyuntikan obat stimulasi ovarium ke pasien serta lebih sedikit pemeriksaan darah dan ultrasonografi, sehingga memungkinkan untuk menjadi suatu pilihan yang disukai oleh pasien. Pasien juga bisa terhindar dari biaya terapi yang lebih mahal serta waktu kontrol yang lama di rumah sakit. Namun demikian, terdapat beberapa masalah yang perlu ditangani terkait metode ini, seperti bagaimana meningkatkan angka keberhasilan serta memastikan keamanan dan mencegah resiko kesehatan pada anak yang akan dilahirkan. Modifikasi pada medium IVM serta pengoptimalan protokol IVM telah meningkatkan hasil pada beberapa penelitian. Penelitian yang lebih mendalam terkait semua aspek yang mempengaruhi maturasi in vitro oosit manusia masih diperlukan menuju penerapan rutin prosedur IVM untuk kelompok pasien tertentu di pusat-pusat pelayanan TRB.Keywords: maturasi in vitro, oosit manusia, fertilisasi in vitro, teknologi reproduksi berbantu